Method for the purification of interferon. - Ling, Tau Chuan; Lin, Yu Kiat; Ooi, Chien Wei; Ariff, Arbakariya (2011)
The present invention discloses a method for the purification of a recombinant microbial Interferon α-2b in an aqueous two-phase system comprising a combination polymer and salt solution. In an embodiment of the present invention, the aqueous two-phase system comprising a combination of polymer and salt solution includes polyethylene glycol (PEG)-potassium phosphate, polyethylene glycol (PEG)-ammonium sulfate, polyethylene glycol (PEG)-sodium carbonate, polyethylene glycol (PEG)-sodium citrate and polyethylene glycol (PEG)-magnesium sulfate. The preferred aqueous two-phase system is the polyethylene glycol (PEG)-potassium phosphate system due to the benefits of low cost and short phase separation time as compared to other systems.